Evasion of Immunological Memory by S. aureus Infection: Implications for Vaccine Design - Teymournejad, Omid; Montgomery, Christopher P. (Frontiers in Immunology, 2021)
Recurrent S. aureus infections are common, suggesting that natural immune responses are not protective. All candidate vaccines tested thus far have failed to protect against S. aureus infections, highlighting an urgent need to better understand the mechanisms by which the bacterium interacts with the host immune system to evade or prevent protective immunity. Although there is evidence in murine models that both cellular and humoral immune responses are important for protection against S. aureus, human studies suggest that T cells are critical in determining susceptibility to infection. This review will use an “anatomical” approach to systematically outline the steps necessary in generating a T cell-mediated immune response against S. aureus. Through the processes of bacterial uptake by antigen presenting cells, processing and presentation of antigens to T cells, and differentiation and proliferation of memory and effector T cell subsets, the ability of S. aureus to evade or inhibit each step of the T-cell mediated response will be reviewed. We hypothesize that these interactions result in the redirection of immune responses away from protective antigens, thereby precluding the establishment of “natural” memory and potentially inhibiting the efficacy of vaccination. It is anticipated that this approach will reveal important implications for future design of vaccines to prevent these infections.